Solving Poisson's Ratio of Single-Layer Composites Acted by Normal Force with Interface Non-Slip Condition. Issue 4 (August 2019) - Li, Yanru; Wang, Liqiang; Jiang, Haibo
Abstract: In this paper, the stress of the interface between the reinforcement and the matrix of composite is analyzed. According to the basic characteristics that the interface does not slip, the strains of the reinforcement and the matrix along the interface are assumed to be equal. The Poisson's ratio calculation formula of the single-layer composite acted by normal force is derived. The research indicates that the interface non-silip of the laminate is the basic feature of the composite. Based on this, the elastic properties of the laminate acted by normal force can be directly calculated and analyzed by equal-strain equations; The Poisson's ratio is not only a function of the Poisson's ratio and volume fraction of the reinforcement and the matrix, but also a function of the ratio of the elastic modulus of the reinforcement to the elastic modulus of the matrix, but the size of Poisson's ratio is independent of the size and shape of the reinforcement and matrix.